STRENTHENING THE LOCAL ECONOMY THROUGH INTERNATIONAL ENTREPRENEURSHIP INITIATIVES IN JATIREJO VILLAGE, LAMONGAN REGENCY - Muhtarom, Abid; Abbas, Ansar; DJ, Yunni Rusmawati; Yaskun, Mohammad; Najiah, Evi Fitrotun; Nurjanah, Fitri (Universitas Pahlawan Tuanku Tambusai, 2023)
Ansar Abbas from Hamdard University Islamabad and the Faculty of Economics, Lamongan Islamic University collaborated for this Community Service activity. Partners in service are residents, especially micro, small and medium enterprises (MSMEs) in Jatirejo Village, Lamongan Regency. As the center of the local economy, MSMEs are very important for the progress of Jatirejo Village in Lamongan Regency. Relevant initiatives to encourage sustainable economic growth are FGDs and entrepreneurship seminars in Jaatirejo Village. The seminar aims to support inclusive economic development in Jatirejo Village. This seminar brings change by giving business people access to new knowledge, creative strategies and business networks. This activity involves seminars and two-way discussions between speakers and participants. This activity was carried out informally with active community participation and was aimed at residents of Kutamekar Village, represented by business actors. Internationally based entrepreneurship seminars motivate, encourage and encourage business people by focusing on business opportunities, marketing strategies, financial management and innovation. These seminars provide a practical guide for business development. This entrepreneurship seminar discusses strategic investments to boost the local economy.